Fatigue assessment in patients with Chronic kidney disease undergoing hemodialysis - كفا , اسمهان حسن (Latakia University Journal -Medical Sciences Series, 2022)
Fatigue is one of the most common symptoms that accompanies Chronic kidney disease (CKD) patients undergoing hemodialysis HD, and affects them psychologically and physically in a way that reduces the quality of their daily life. Therefore, the aim of the current descriptive study was to assess fatigue in 50 CKD patients undergoing HD. In the dialysis department of the General Authority of Damascus Hospital, they were selected using the convenient sample method, and the data were collected using the Fatigue Scale in the Greek version translated into Arabic. The results of the study showed that about two thirds of patients suffer from fatigue after HD, and about a quarter of them have severe fatigue, and there was a statistically significant relationship between the degree of fatigue in patients and each of the variables of age, educational level, social status and work. The study recommended conducting close monitoring of patients' adherence to the diet and prescribed treatment, and making adjustments in the patient's environment, activities and food pattern to maintain his health and fitness to reduce fatigue, and re-applying the study to a larger sample.